Misurare l'onestà di un discorso politico: Contesti comunicativi a confronto: comizio, parlamento, assemblea di partito - Davitti, Lucrezia (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2025)
This study centers on political discourse, with a particular focus on the implicit linguistic constructions speakers use to influence undecided or inattentive voters, effectively bypassing their critical evaluation. The research adopts a corpus-based approach, drawing on the IMPAQTS corpus, which is representative of political speech in the history of the Italian Republic. The sub-sample analyzed includes speeches by Anna Maria Bernini, Pier Luigi Bersani, Carlo Calenda, Vincenzo De Luca, Luigi De Magistris, Luigi Di Maio, Nicola Fratoianni, Gioriga Meloni, Matteo Renzi, and Matteo Salvini. A method for calculating a text’s implicitness index was applied to the selected speeches. The results were then used to compare both individual speakers and different communicative contexts